Bedrock exfiltration as a triggering mechanism for shallow landslides. Issue 9 (4th September 2013) - Brönnimann, Cornelia; Stähli, Manfred; Schneider, Philipp; Seward, Linda; Springman, Sarah M.
<x xml:space="preserve">Abstract</x> [1] Shallow landslides pose substantial risks to people and infrastructure in mountain areas. Their occurrence is influenced by groundwater dynamics and bedrock characteristics. The bedrock may drain or contribute to groundwater in the overlying soil mass, depending on the hydraulic conductivity, degree of fracturing, saturation, and hydraulic head. Here, we present a detailed case study for a slope from Central Switzerland, where soil‐bedrock interactions were responsible for triggering shallow landslides in the past. The bedrock in the study area represents a succession of heavily fissured conglomerate‐sandstone beds and weathered marlstone layers, which are overlain by a clayey soil layer. There is evidence of a temporally confined aquifer in bedrock fractures from a severe storm event in August 2005. We derived a detailed geological model of the slope from electrical resistivity tomography surveys, borehole data, and bedrock outcrops. Then, the groundwater response to 32 rainfall events was monitored in the soil layer and in different bedrock layers from November 2010 to November 2011. We observed a fast and substantial rise of the hydraulic head in the bedrock, which was in contrast to the low permeability of the soil layer. The data suggest that rapid groundwater flow through bedrock fractures caused the immediate increase of the hydraulic head. Our observations document how water pressure builds up in fractured bedrock below a low permeability soil cover during heavy rainfall, which may trigger shallow landslides.